Comparison of Lactobacillus crispatus isolates from Lactobacillus-dominated vaginal microbiomes with isolates from microbiomes containing bacterial vaginosis-associated bacteria - Abdelmaksoud, Abdallah A. (Microbiology (Reading), 2016)
Vaginal lactobacilli can inhibit colonization by and growth of other bacteria, thereby preventing development of bacterial vaginosis (BV). Amongst the lactobacilli, Lactobacillus crispatus appears to be particularly effective at inhibiting growth of BV-associated bacteria. Nonetheless, some women who are colonized with this species can still develop clinical BV. Therefore, we sought to determine whether strains of L. crispatus that colonize women with lactobacilli-dominated vaginal microbiomes are distinct from strains that colonize women who develop BV. The genomes of L. crispatus isolates from four women with lactobacilli-dominated vaginal microbiomes ( < 1 % 16S rRNA reads above threshold from genera other than Lactobacillus) and four women with microbiomes containing BV-associated bacteria (>12 % 16S rRNA reads from bacterial taxa associated with BV) were sequenced and compared. Lactic acid production by the different strains was quantified. Phage induction in the strains was also analysed. There was considerable genetic diversity between strains, and several genes were exclusive to either the strains from Lactobacillus-dominated microbiomes or those containing BV-associated bacteria. Overall, strains from microbiomes dominated by lactobacilli did not differ from strains from microbiomes containing BV-associated bacteria with respect to lactic acid production. All of the strains contained multiple phage, but there was no clear distinction between the presence or absence of BV-associated bacteria with respect to phage-induced lysis. Genes found to be exclusive to the Lactobacillus-dominated versus BV-associated bacteria-containing microbiomes could play a role in the maintenance of vaginal health and the development of BV, respectively.